Dimethylarginines in pediatric CKD: clinical utility of ADMA and SDMA as biomarkers - Nalçacıoğlu, Hülya; Cihan, Murat; Önal, Hülya Gözde; Karalı, Demet Tekcan (Frontiers in Pediatrics, 2025)
IntroductionPediatric chronic kidney disease (CKD) often presents no symptoms in its early stages, making timely diagnosis challenging. Asymmetric dimethylarginine (ADMA) and symmetric dimethylarginine (SDMA) are methylated arginine derivatives that reduce nitric oxide availability and have been suggested as potential early indicators of kidney dysfunction. This study aimed to evaluate the usefulness of ADMA and SDMA in pediatric CKD and to assess their association with renal function and disease severity.MethodsThis single-center, cross-sectional, observational study enrolled 100 children aged 1–18 with CKD stages 2–4 and 70 healthy, age- and sex-matched controls between January and September 2023. Serum ADMA and SDMA levels were measured using ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-ESI-MS/MS). The estimated glomerular filtration rate (eGFR) was calculated using the Schwartz formula. Comparisons were made between groups and CKD stages, and correlation analyses were conducted with eGFR.ResultsADMA and SDMA levels were significantly higher in the CKD group than in the control group (p < 0.001 and p = 0.013, respectively), while the ADMA/SDMA ratio showed no significant difference. ADMA levels increased progressively with CKD stage, particularly in stage 4 patients (p < 0.001). There were moderate negative correlations between eGFR and both ADMA (r = −0.380, p < 0.001) and SDMA (r = −0.238, p = 0.002). These findings suggest that both biomarkers increase with disease progression, with ADMA demonstrating moderate associations.ConclusionSerum ADMA and SDMA levels increase with worsening kidney function in children and may serve as useful markers associated with disease severity in pediatric CKD, but further validation is required. In particular, ADMA reflects disease severity and endothelial dysfunction, highlighting its potential role in clinical risk stratification.